Differentiating Grapes from Wine: The Education-To-Work Transition - Donald, William E.; Healy, Michael (GILE Journal of Skills Development, 2024)
There is a growing interest in connecting the literature on graduate employability, career development, and worker employability. However, inconsistent terminology across these fields poses a challenge. This essay focuses on the term ‘school-to-work transition’. In career development and worker employability literature, it often refers to the movement from all stages of schooling into the labour market, while in graduate employability literature it is understood to only refer to the transition from secondary school into the labour market. To illustrate this issue, we use a metaphor comparing grapes to wine. Consequently, we propose ‘education-to-work transition’ as an overarching term, with various subcategories specific to secondary and tertiary education.